Clinical Pharmacogenetics Implementation Consortium (CPIC) Guidelines for Ivacaftor Therapy in the Context of CFTR Genotype. Issue 6 (5th March 2014) - Clancy, J P; Johnson, S G; Yee, S W; McDonagh, E M; Caudle, K E; Klein, T E; Cannavo, M; Giacomini, K M
<x xml:space="preserve">Abstract</x> Cystic fibrosis (CF) is a life‐shortening disease arising as a consequence of mutations within the CFTR gene. Novel therapeutics for CF are emerging that target CF transmembrane conductance regulator protein (CFTR) defects resulting from specific CFTR variants. Ivacaftor is a drug that potentiates CFTR gating function and is specifically indicated for CF patients with a particular CFTR variant, G551D‐CFTR (rs75527207). Here, we provide therapeutic recommendations for ivacaftor based on preemptive CFTR genotype results. Clinical Pharmacology & Therapeutics (2014); 95 6, 592–597. doi:10.1038/clpt.2014.54